Performance evaluation on EZW & WDR image compression techniques - Raja, S P; Suruliandi, A (2010 IEEE International Conference on Communication Control and Computing Technologies, 2010)
The objective of this paper is to implement the concept of wavelet based image compression to gray scale images using different techniques. The techniques involved in the comparison process are EZW and WDR. These techniques are more efficient and provide a better quality in the image. In compression, wavelets have shown a good adaptability to a wide range of data, while being of reasonable complexity. Wavelet difference reduction (WDR) has recently been proposed as a method for efficient embedded image coding. This method retains all of the important features like low complexity, region of interest, embeddedness, and progressive SNR. The above techniques have been successfully used in many applications. The techniques are compared by using the performance parameters PSNR and MSE. Images obtained with those techniques yield very good results.